Pengolahan Limbah Serbuk Kayu Melalui Eksperimen Tekstur untuk Menemukan Material Baru - sekar, Anastasia Christabel; Hairunnas, Hairunnas; Sujatmiko, Guguh (SPACEPRO: Product Design Jurnal, 2025)
The growth of the wood processing industry in Indonesia, which reached 8.04% in 2021, also increased the amount of sawdust waste that has not been optimally managed. This waste is generally produced from the process of cutting and sawing wood, and can reach tens of tons per day in industrial centers such as Jepara and Pasuruan. If not utilized, sawdust can cause air pollution, pollute the surrounding environment, and become a source of material waste. In fact, sawdust has the potential as an alternative raw material in the manufacture of building materials and design products. This study aims to explore the utilization of sawdust waste by mixing it with adhesives, such as resin and white glue, to produce solid materials that have utility value and durability. Experiments were carried out with various compositions to study material performance, especially in terms of heat resistance. The results of this study are expected to be a creative and applicable solution in the processing of sawdust waste, while supporting the development of environmentally friendly and economically valuable sustainable designs in the future.